The perception of public spaces in Mexico city, a governance approach - Sergio Alvarado Vazquez; Cesar Casiano Flores (Journal of Urban Management, 2022)
Public spaces are considered a vital ingredient of prosperous cities as they support their sense of community, identity and culture. Understanding their relevance, the Mexican government has developed new regulatory frameworks. In 2016, the first federal legislation in Mexico was created and combined the concepts of urban development, public space, and social participation. This change affected national and local regulations. Acknowledging that public spaces are anchored to the institutional and governance context, we based our explorative research from a theoretical perspective on the Contextual Interaction Theory (CIT) and its five governance elements. Considering the regulatory and institutional framework for public spaces in Mexico, this research aims to understand how the different actors perceive the current conditions of public spaces in Mexico City. This research adopted a case study approach, and we conducted eight semi-structured interviews with stakeholders that participate in the planning process of public spaces in Mexico City. Through these interviews and revision of secondary sources, we found that all interviewed actors agree that the regulatory framework of public spaces differs with the application in practice, with legal gaps and lack of clarity in responsibilities which brings confusion among practitioners and developers of public space projects. The implementation of the public spaces policy is affected by the lack of continuity of public space projects and the discrepancies between the efforts to promote inclusive and safe public spaces, and a negative perception of society on the current conditions of public spaces.
Keywords: 710; Governance; Mexico; Policy implementation; Public open spaces